Pemanfaatan Aplikasi Powtoon Sebagai Sumber Belajar Speaking - Tities Hijratur Rahmah; Enis Fitriani; Adi (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Some students have difficulty in speaking English, and this happens because of various problems. One ofthe problems is vocabulary and pronunciation. Based on theproblems stated, this study aims to explain the use ofthe Powtoon application as one of the learning resources needed by students.Powtoonis one of alternativeapplication learning speaking for students now days. Powtoon application can improve student’s speaking abilitybecause Powtoon application is a cartoon learning video that very interesting.